Feeding tolerance to a running gut-challenge protocol: a cross-sectional exploration - Martinez, I. G.; Biesiekierski, J. R.; Rauch, C. E.; Costa, R. J. S. (International Journal of Sports Medicine, 2025)
This study examined gastrointestinal function, substrate utilization, and exercise performance differences in response to a gut-challenge between (1) female and male athletes, (2) young adult versus masters athletes, and (3) athletes with or without exercise-associated gastrointestinal symptom history (Ex-GIS). Fifty-three endurance athletes (43 males and 10 females) completed a gut-challenge involving a 2-hour run (60% V?O2max) with 90 g/h carbohydrate intake, followed by a 1-hour self-paced distance test (DT) with ad libitum water. Blood and breath samples were collected pre- and post-exercise. Blood glucose and substrate utilization during exercise were measured, while Ex-GIS and feeding tolerance were assessed pre-, during, and post-exercise. Interest in food and appetite during exercise was lower in symptomatic athletes than asymptomatic athletes (p<0.05). Females had a higher blood glucose concentration during exercise (p=0.037) and immediately after exercise (p=0.003) and a lower whole-body fat oxidation rate during exercise (p=0.009). Exercise performance did not differ based on the biological sex, age, and Ex-GIS history. Overall, gastrointestinal functional markers were comparable between groups, while feeding tolerance and substrate availability and utilization appear to be influenced by the Ex-GIS history and biological sex, respectively. Tailored management of gastrointestinal issues in athletes should be based on an individual basis as opposed to general demographic characteristics.